Financial Determinants of Firm Value in Indonesia's Energy Sector: The Role of Intellectual Capital, Sales Growth, and Firm Size - Sari, Intan Rahma; Astuti, Reni; Peshar, Fateh Rizkiah (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study examines the impact of intellectual capital, sales growth, and firm size on firm value in energy-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using panel data regression with the Common Effect Model (CEM), 35 companies were selected through purposive sampling. Intellectual capital was measured using the Value Added Intellectual Coefficient (VAIC), while sales growth and firm size were proxied by revenue growth and total assets, respectively. Firm value was assessed using the Price to Book Value (PBV) ratio. None of the independent variables have a statistically significant effect on firm value, either partially or simultaneously. These findings contrast with prior studies and suggest that firm value in capital-intensive sectors may be more influenced by external factors such as market volatility or regulatory policies. The study recommends that future research integrate both internal and external determinants better to explain firm value dynamics in the energy industry.